(untitled) (Philologia, 2021)
This paper is motivated by a number of manipulative strategies used in an election discourse. The methods of hidden influence in the sphere of political discourse were examined in this research. Our interests concern the phenomena of language manipulation. There is a great number of language manipulation tricks that vary in their nature. This article takes into consideration an “image” as a way of controlling our consciousness and behavior. The image studies deal with creating images. These images are used to build an ideal portrait of a person. In political discourse this person is a politician in search for power. Within the boundaries of this article, images were divided into two groups: those which are borrowed and those which are part and parcel of the personality of a politician. The research resulted in revealing the most popular and effective “borrowed” images.